Picture Word Inductive Model (PWIM) on Students’ Vocabulary Achievement and Attitude - Bermillo, Joanne Echalico; Remollo, Emelda Roma (Indonesian Journal of Contemporary Education, 2022)
Picture Word Inductive Model (PWIM) is an inquiry-based vocabulary strategy which uses pictures to transmit information to the learners. This study investigated how PWIM affected the vocabulary achievement and attitude of the Grade 8 students. There were 50 participants of the study, 25 from the group exposed to PWIM and 25 from the group not exposed to PWIM. The vocabulary achievements of the students were identified using the 64-item teacher-made pre-test, posttest, and retention test. Students’ attitudes towards vocabulary learning were determined through a 20-item Likert-Scale Questionnaire on The Learners’ Attitude Towards Vocabulary Learning adapted from Gimolatan (2016). Results showed that the group exposed to PWIM strategy outperformed the unexposed group in vocabulary achievement in terms of posttest and retention test. Non-PWIM strategy was able to increase the students’ vocabulary achievement, but the increase was not as high as of the learners exposed to PWIM. Also, the students exposed to PWIM improved their attitude towards vocabulary learning from moderately positive to positive attitude while the group not exposed to PWIM remained to have a moderately positive attitude. Moreover, the vocabulary achievement of students exposed to PWIM was significantly higher than the students who were not exposed to PWIM. There was also a significant difference on the attitude of the students exposed and not exposed to PWIM towards vocabulary learning. Thus, PWIM was effective in improving the students’ vocabulary achievement as well as in enhancing their attitude towards vocabulary learning.